A novel interleukin-10 DNA mucosal delivery system attenuates intestinal inflammation in a mouse model - del Carmen, Silvina Andrea (2013)
Inflammatory bowel diseases (IBD) describe a group of complex intestinal disorders characterized by inflammation in the gastrointestinal tract. Current treatments for IBD include the use of anti-inflammatory drugs; furthermore, recombinant lactic acid bacteria have been used as a therapeutic vehicle for anti-inflammatory agents in IBD models. Interleukin-10 (IL-10) is one of the most important anti-inflammatory cytokines; however, its oral administration is limited because it is quickly degraded in the gastrointestinal tract and systemic treatments have led to undesirable side effects. In this study, an engineered invasive strain of Lactococcus (L.) lactis producing Fibronectin Binding Protein A (FnBPA+), from Staphylococcus aureus capable of delivering, directly inside eukaryotic cells, an eukaryotic DNA expression vector containing the ORF coding for IL-10 of Mus musculus (pValac:il-10) was developed and its functionality was evaluated using in vitro and in vivo assays. Functionality of the plasmid and the invasive strain was demonstrated by transfection and invasiveness assays using cell cultures and in vivo in mice by fluorescence microscopy. TNBS inoculated mice that received this novel strain showed lower damage scores in their large intestines (at both macroscopic and microscopic levels), lower microbial translocation to liver, and increased anti-inflammatory/pro-inflammatory cytokine ratios compared to mice that received L. lactis FnBPA+ without the pValac:il-10 plasmid. The effectiveness was demonstrated of this novel DNA delivery therapeutic strategy in the prevention of inflammation using a murine model of colitis.